Desigualdad de la incertidumbre económica subjetiva y perspectivas económicas individuales durante la pandemia; Inequality of subjective economic uncertainty and individual economic prospects in the pandemic period - Montserrat Guillén; Miguel Santolino; Xenxo Vidal-Llana (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– This article studies which factors influence the appearance of subjective economic uncertainty and what are the economic expectations of individuals. The impact of the pandemic on the household economy and the subjective uncertainty based on a set of socioeconomic factors that cannot be observed in macroeconomic studies on uncertainty are analyzed. We use data from a survey conducted in October 2021 taking a representative sample of Catalonia (Spain). The results suggest that individuals in households with greater saving capacity are those who express less uncertainty regarding their future economic situation and women show greater future uncertainty than men. This study finds evidence that there is an association between age and economic expectations, with older people being the most pessimistic. However, age is not associated with a greater presence of subjective uncertainty, so we can conclude that there has not been a deterioration of confidence in the elderly.
Keywords: C83; D14; D31; G41; 330; Economic behavior; expectations; survey; pandemic; inequality